PRE-SCHOOLER QUESTIONS ENCOURAGING COGNITION - Stangaine, Inga; Augstkalne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
When pre-schooler learns language, development of his cognitive processes changes, ability to classify and generalise rises. Child’s needs and interests encourage him to ask, answer, think, act. Word meanings are used and sought in various speech situations, especially when expressing all known, unknown, understood, not understood verbally. Asking and answering questions requires certain vocabulary, ability to formulate thoughts and find contact with communication partner in dialogue.Aim: study of the pre-schooler question content, influence thereof on formation of cognitive interests.Methods and materials: analysis of theoretical literature, observations, conversations with children, writing down and analysing their spontaneous questions and creating question situations. Pre-schooler questions and their variety was analysed grouping by various criteria, reflecting diversity of children interests and ability to understand meaning of different words. Conclusions: progress of pre-schooler cognitive interests is expressed in their questions. When asking questions, child’s vocabulary becomes more expanded, which is related to the fact that perception of the world around us is enlarged and deepened. Adult responsiveness, ability to listen, patience in seeking answers, explaining unclear, encouraging to think and ask the next questions all are significant factors encouraging child’s cognitive interests.